2012
DOI: 10.1371/journal.pone.0046387
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Induction of Sox21 Regulates Sensory Cell Formation in the Embryonic Chicken Inner Ear

Abstract: During embryonic development, hair cells and support cells in the sensory epithelia of the inner ear derive from progenitors that express Sox2, a member of the SoxB1 family of transcription factors. Sox2 is essential for sensory specification, but high levels of Sox2 expression appear to inhibit hair cell differentiation, suggesting that factors regulating Sox2 activity could be critical for both processes. Antagonistic interactions between SoxB1 and SoxB2 factors are known to regulate cell differentiation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…The function of Sox21 , the SoxB2 vertebrate’s ortholog, has been mostly studied in fish, chicken and mouse. In chicken, it has a neurogenic function and it is expressed in vestibular and auditory organs, being an important regulator of sensory cell differentiation [ 8 , 9 ]. In Xenopus laevis , Sox21 is expressed in several regions of the central nervous system (CNS) and in the sensory organs [ 4 ], similarly to chicken [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The function of Sox21 , the SoxB2 vertebrate’s ortholog, has been mostly studied in fish, chicken and mouse. In chicken, it has a neurogenic function and it is expressed in vestibular and auditory organs, being an important regulator of sensory cell differentiation [ 8 , 9 ]. In Xenopus laevis , Sox21 is expressed in several regions of the central nervous system (CNS) and in the sensory organs [ 4 ], similarly to chicken [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mutational inactivation of Sox21 shows only mild effects in hair cells with an increase in their number in some homozygous animals combined with disorganized polarity. In the chick inner ear, which displays a similar Sox21 expression pattern, overexpression at different stages leads to different results (Freeman and Daudet 2012). Retrovirus-mediated misexpression reduces Sox2 and Prox1 (prospero homeobox 1) expression and prevents neuron and hair cell differentiation as analyzed by TuJ1 IHC, which in the chick embryo labels both cell types.…”
Section: Sox and Proneural Bhlh Proteins In Neuron And Hair Cell Prodmentioning
confidence: 99%
“…In sharp contrast, 92.1% of non‐sensory cells transfected with pCIG.cAtoh1.IRES.nucEGFP developed as hair cells ( n = 419; Figures B′, 3B″ and 3D). Detailed examination of these ectopic hair cells revealed that they possessed stereocilia bundles (the base of which is labelled with HCA; Figure C′), and cytoplasmic localisation of otoferlin revealed the classic flask shape that is observed in mature vestibular hair cells (Figure C″) (Freeman and Daudet, ). We observed the presence of ectopic hair cells in all non‐sensory regions that were transfected; however, it must be noted that transfection was consistently concentrated in the two maculae and the ampullas of the semicircular canals.…”
Section: Resultsmentioning
confidence: 99%